Ultrasound imaging in floppy eyelid syndrome: anatomical and clinical considerations - Batis Vasilios; Detorakis Efstathios; Schiza Sophia; Prokopakis Emmanuel; Krasagakis Konstantinos; Drakonaki Elena (Journal of Ultrasonography)
Skin ultrasonography and elastography provide information on superficial tissue anatomy and elasticity. Floppy eyelid syndrome is characterized by eyelid hyperlaxity and is associated with several ophthalmic and systemic conditions, such as obstructive sleep apnea. This study evaluates the diagnostic role of ultrasonography and elastography in floppy eyelid syndrome.